The Implemetation genetic algorithm Timun Mas Game - Indah Permatasari; Muchamad Fajri Amirul Nasrullah (Politeknik Negeri Batam, 2019)
Timun Mas Game was inspired by a fairy tales story from Cental Java. It is fairy tale of Timun Mas. This game will makes the player has an experience and missions as Mbok Sarni who is the part of the original storyline. Therefore the game genre is Role Playing Game (RPG). The game story has 2 missions, first the player needs to plant the seed of Timun and collect all magical weapons to attack Buto Ijo. In this undergraduated thesis, the author designed the first mission of Timun Mas Game, which is planting the seed of Timun Mas until it was grow up The Planting activities are watering and fertilizing seeds until it is grow up to golden Cucumber. During the planting process, there will be rats as pest that attack the growth of seed. Player need to eliminate the pest by using the hammer that provide from system. The pest is a NPC (Non Player Character) that was controlled by an artificial Intelligence using a monodevelop while the game environment is built with unity 5.4.1f1 (64-bit) game engine. The type of artificial intelligent that was used to create an intelligence system is Genetic Algorithm (GA). It has a function to maximize genes in the chromosome strength on the NPC including attack power, speed of movement, and health point of the pest which is affected by player behaviour/action. The dynamic changes of pest's strength will affected the difficulty level of the game that will be useful to make a good experience for the player as the main goal of this research.